Sustainable livelihood among women: A study on social, financial, physical, human capital and natural assets. - Ab Rani, Nor Zuriati Amani; Azizan, Nurul Hafizah; Zahari, Nor Sabrina; Abd Hadi, Nur Azureen; Husin, Suraya; Mat Rusok, Nur Hazelen; Che Mat, Rosfatihah (Journal of Islamic, Social, Economics and Development, 2025)
This study explores sustainable livelihood among women using the Sustainable Livelihood Framework, which consists of five core capital assets:social, financial, physical, human capital and natural assets. Women play a critical role in sustaining family well-being, managing household resources, and contributing to community resilience. Using a quantitative descriptive approach, data were collected via a structured questionnaire among women across various demographic backgrounds and residential area. The data were analyzed using descriptive statistics to examine the livelihood assets among women. Findings indicate that strong social relationships, stable income, higher education levels, access to infrastructure, good health, clean water and a healthy environment in daily lives significantly influence the livelihood resilience of women. This study highlights the importance of empowering women by enhancing access to multiple livelihood assets, which are essential for achieving a sustainable and balanced life.